Herbal Medicine AC591 Prevents Oxaliplatin-Induced Peripheral Neuropathy in Animal Model and Cancer Patients - Cheng, Xiaolan; Huo, Jiege; Wang, Dawei; Cai, Xueting; Sun, Xiaoyan; Lu, Wuguang; Yang, Yang; Hu, Chunping; Wang, Xiaoning; Cao, Peng (Frontiers in Pharmacology, 2017)
Oxaliplatin is clinically compelling because of severe peripheral neuropathy. The side effect can result in dosage reductions or even cessation of chemotherapy, and no effective treatments are available. AC591 is a standardized extract of Huangqi Guizhi Wuwu decoction (HGWD), an herbal formula recorded in “Synopsis of the Golden Chamber” for improving limb numbness and pain. In this study, we investigated whether AC591 could protect against oxaliplatin-induced peripheral neuropathy. To clarify it, a rat model of oxaliplatin-induced peripheral neuropathy was established, and neuroprotective effect of AC591 was studied. Our results showed that pretreatment with AC591 reduced oxaliplatin-induced cold hyperalgesia, mechanical allodynia as well as morphological damage of dorsal root ganglion. Microarray analysis indicated the neuroprotective action of AC591 depended on the modulation of multiple molecular targets and pathways involved in the downregulation of inflammation and immune response. Moreover, AC591 enhanced the antitumor activity of oxaliplatin to some extent in Balb/c mice bearing CT-26 carcinoma cells. The efficacy of AC591 is also investigated in 72 colorectal cancer patients. After four cycles of treatment, the percentage of grades 1-2 neurotoxicity in AC591-treated group (n=36) was 25%, whereas in the control group the incidence was 55.55% (P < 0.01) (n=36). No significant differences in the tumor response rate between the two groups were found. These evidences suggested that AC591 can prevent oxaliplatin-induced neuropathy without reducing its antitumor activity, and may be a promising adjuvant to alleviate sensory symptoms in clinical practice.